A patatin-like phospholipase functions during gametocyte induction in the malaria parasite Plasmodium falciparum - Flammersfeld, Ansgar; Panyot, Atscharah; Yamaryo‐Botté, Yoshiki; Aurass, Philipp; Przyborski, Jude M.; Flieger, Antje; Botté, Cyrille; Pradel, Gabriele (Cellular microbiology, 2020)
Patatin-like phospholipases (PNPLAs) are highly conserved enzymes of prokaryotic and eukaryotic organisms with major roles in lipid homeostasis. The genome of the malaria parasite Plasmodium falciparum encodes four putative PNPLAs with predicted functions during phospholipid degradation. We here investigated the role of one of the plasmodial PNPLAs, a putative PLA2 termed PNPLA1, during blood stage replication and gametocyte development. PNPLA1 is present in the asexual and sexual blood stages and here localizes to the cytoplasm. PNPLA1-deficiency due to gene disruption or conditional gene-knockdown had no effect on intraerythrocytic growth, gametocyte development and gametogenesis. However, parasites lacking PNPLA1 were impaired in gametocyte induction, while PNPLA1 overexpression promotes gametocyte formation. The loss of PNPLA1 further leads to transcriptional down-regulation of genes related to gametocytogenesis, including the gene encoding the sexual commitment regulator AP2-G. Additionally, lipidomics of PNPLA1-deficient asexual blood stage parasites revealed overall increased levels of major phospholipids, including phosphatidylcholine (PC), which is a substrate of PLA2. PC synthesis is known to be pivotal for erythrocytic replication, while the reduced availability of PC precursors drives the parasite into gametocytogenesis; we thus hypothesize that the higher PC levels due to PNPLA1-deficiency prevent the blood stage parasites from entering the sexual pathway.
First published: 16 November 2019
Gesehen am 29.06.2020